Generalized host‐plant feeding can hide sterol‐specialized foraging behaviors in bee–plant interactions - Vanderplanck, Maryse (Ecol Evol, 2019)
Host‐plant selection is a key factor driving the ecology and evolution of insects. While the majority of phytophagous insects is highly host specific, generalist behavior is quite widespread among bees and presumably involves physiological adaptations that remain largely unexplored. However, floral visitation patterns suggest that generalist bees do not forage randomly on all available resources. While resource availability and accessibility as well as nectar composition have been widely explored, pollen chemistry could also have an impact on the range of suitable host‐plants. This study focuses on particular pollen nutrients that cannot be synthesized de novo by insects but are key compounds of cell membranes and the precursor for molting process: the sterols. We compared the sterol composition of pollen from the main host‐plants of three generalist bees: Anthophora plumipes, Colletes cunicularius, and Osmia cornuta, as well as one specialist bee Andrena vaga. We also analyzed the sterols of their brood cell provisions, the tissues of larvae and nonemerged females to determine which sterols are used by the different species. Our results show that sterols are not used accordingly to foraging strategy: Both the specialist species A. vaga and the generalist species C. cunicularius might metabolize a rare C(27) sterol, while the two generalist species A. plumipes and O. cornuta might rather use a very common C(28) sterol. Our results suggest that shared sterolic compounds among plant species could facilitate the exploitation of multiple host‐plants by A. plumipes and O. cornuta whereas the generalist C. cunicularius might be more constrained due to its physiological requirements of a more uncommon dietary sterol. Our findings suggest that a bee displaying a generalist foraging behavior may sometimes hide a sterol‐specialized species. This evidence challenges the hypothesis that all generalist free‐living bee species are all able to develop on a wide range of different pollen types.